PENGARUH HARGA, NILAI MANFAAT, DAN KUALITAS TERHADAP KEPUASAN PELANGGAN HANDPHONE BLACKBERRY DI SURABAYA - Maretia Mega T.; Soni Harsono (STIE Perbanas Surabaya, 2013)
This research aims to find out whether there is a relationship between the prices partially and a Blackberrys customer satisfaction, the previewed value and a Blackberrys customer satisfaction, and the quality and a Blackberrys customer satisfaction in Surabaya. Besides that, it also attempts to reveal whether there is a relationship between price, perceived value, and quality simultaneously and a Blackberrys customers satisfaction in Surabaya. Analysis is done by means of multiple linear regression analysis in SPSS 16.0. This study took 100 people as the respondents for getting the data which was conducted in Surabaya with a sample of the Blackberry users who have been using a Blackberry for at least 6 months. The sample technique is convenience sampling. It shows price significantly affects customer satisfaction; the perceived value has no effect on the customer satisfaction. Yet, quality significantly affects customer satisfaction. Simultaneously, price, perceived value, and quality affect the customer satisfaction.